2005
DOI: 10.1143/jjap.44.688
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO Nanorods by Laser Ablation of ZnO and Zn Targets in He and O2 Background Gas

Abstract: A new continuous impingement mixing process has been used to disperse unpurified single-walled carbon nanotubes (SWNTs) in a Shell EPON-862/EpiCURE system. Composites with up to 0.2 wt% loading of SWNTs were prepared by this process. The hydrodynamic dispersion of SWNTs was found to depend on the non-dimensional Curtet number (C t ). Dispersion was evaluated by analyzing SEM images of the fracture surface using an image processing technique based on the concept of Shannon entropy. Electrical conductivity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…This behavior can be attributed to the low lattice mismatch between ZnO and GaN. Okada et al have also shown the change in morphology and orientation of ZnO nanostructures with respect to substrates . This implies that the morphologies of ZnO nanostructures can be tuned during growth by utilizing the lattice mismatch between the substrate and film.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This behavior can be attributed to the low lattice mismatch between ZnO and GaN. Okada et al have also shown the change in morphology and orientation of ZnO nanostructures with respect to substrates . This implies that the morphologies of ZnO nanostructures can be tuned during growth by utilizing the lattice mismatch between the substrate and film.…”
Section: Resultsmentioning
confidence: 98%
“…Among them, ZnO nanostructures, which have a bandgap of 3.37 eV and an exciton binding energy of 60 meV, have potential applications in nanoelectronics , nano-optelectronics , nanopiezotronics , gas/chemical sensors , transparent electrodes , and field emission devices . Various forms of ZnO nanostructures, including nanorods , , nanowalls , nanowires , nanobelts , and quantum dots , have been reported using physical and chemical deposition techniques. In comparison with ZnO nanorods/wires, the growth of two-dimensional (2D) ZnO nanowalls are difficult due to its polar structure along the c -axis.…”
Section: Introductionmentioning
confidence: 99%
“…However, only few efforts have been made to employ this method in the synthesis of nanostructured ZnO crystals such as nanowires. We have successfully grown nondoped ZnO nanowires by a newly developed nanoparticle-assisted pulsedlaser deposition (NAPLD) technique that does not require the use of any catalyst [6][7][8][9]. And we also found and demonstrated that these crystals had good crystallinity from low-temperature photoluminescence (PL) measurements [10,11].…”
Section: Introductionmentioning
confidence: 94%
“…EXPERIMENTAL PROCEDURE P-doped ZnO nanowire crystals were synthesized by the newly developed NAPLD technique [6][7][8][9]. Sintered ZnO tablets mixed with 5 or 2 wt% P 2 O 5 were used as the source material for the synthesis of P-doped ZnO nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…The first is control of nanowire growth direction, shape, density, and position etc. In our study, we have succeeded in synthesizing various nanostructures, such as the vertically and horizontally aligned ZnO nanowires [23][24][25] nanorods [26][27][28][29] , and nanowalls [30] by nanoparticle-assisted pulsed-laser deposition (NAPLD) without any catalyst. Besides, the density-controlled growth of vertically aligned ZnO nanowires has been successfully achieved by varying substrate -target distance, repetition rate, and laser energy [25] .…”
Section: Introductionmentioning
confidence: 99%